A novel nonsense mutation in keratin 10 causes a familial case of recessive epidermolytic ichthyosis. Issue 2 (15th April 2013) - Gutierrez, Jeydith A.; Hannoush, Zeina C.; Vargas, Luis G.; Momany, Allison; Garcia, Carmen C.; Murray, Jeffrey C.; Dunnwald, Martine
Abstract Epidermolytic ichthyosis (EI) is a rare skin disorder characterized by generalized erythroderma and cutaneous blistering at birth, which is substituted by hyperkeratosis later in life. It is caused by autosomal dominant mutations in highly conserved regions of KRT1 and KRT10. To date, only four mutations with autosomal recessive inheritance of EI have been described in consanguineous families. All of them affect the 2B domain of KRT10. In the present study, we describe four patients with EI (including one lethal case) born from unaffected parents in a consanguineous family of a native Venezuelan community. The objective of this study was to characterize the clinical, genetic, and morphological aspects of the disease in this family, as well as understand its functional implications. Genomic DNA was sequenced for KRT10 and KRT1. Immunofluoresence for keratin expression was performed on cutaneous biopsies. After examination of cutaneous biopsies histology, our results showed hyperkeratosis and acantholysis with an expanded granular layer. Sequencing of KRT10 demonstrated a nonsense mutation (p.Tyr282Ter.) corresponding to the 1B domain of the protein in patients and a heterozygous pattern in other family members, resulting in complete absence of K10. The loss of K10 was compensated by upregulation of K14 and K17. In conclusion, this novel mutation in KRT10 is the first recessive genetic variation that is not located in the so called "hot spot" for recessive EI, suggesting that other areas of the gene are also susceptible for such mutations.